Plural Imagination: Diversity in Mind and Making. Issue 3 (3rd July 2022) - MacKisack, Matthew; Aldworth, Susan; Macpherson, Fiona; Onians, John; Winlove, Crawford; Zeman, Adam
Abstract: The experience of visual mental imagery—seeing in the mind's eye—varies widely between individuals, but perhaps because we tend to assume our own way of thinking to be everyone's, how this crucial variation impacts art practice, and indeed art history, has barely been addressed. We seek to correct this omission by pursuing the implications of how artists with aphantasia (the absence of mental imagery) and hyperphantasia (imagery of extreme vividness) describe their working processes. The findings remind us of the need to challenge normative, universalizing models of art making and art maker.